KEDUDUKAN TENAGA MENENGAH KEFARMASIAN DALAM DIMENSI PERATURAN TENAGA KESEHATAN DAN KEFARMASIAN - I Made Adi Widnyana; IB. Sudarma Putra; DA. Istri Krisna Dewi (VYAVAHARA DUTA, 2022)
There has been a conflict of norms betweenGovernment Regulation Number 51 of 2009 concerning Pharmaceutical Work and Law Number 36 of 2014 concerning Health Workers. The existence of this conflict of norms causes problems in the practice of pharmaceutical services in the field so that this provides legal uncertainty, especially for pharmacists with high school certificates to carry out their practice. Therefore, it is necessary to conduct an assessment and analysis based on legal theory so as to be able to provide certainty for pharmacists with vocational high school certificates who have carried out professional practice.This writing uses a normative research method with a statutory and historical approach. The tiered legal theory states that law is always formed and abolished by the competent authorities to form it based on higher rules, so that lower (inferior) rules can be formed based on higher (superior) rules. Therefore, the position of Pharmaceutical Health Workers refers to Law No. 36 of 2014 not on Government Regulations, so that the position of Pharmaceutical Health Workers who still have a vocational high school diploma who previously worked as a health worker is now changed to an assistant health worker.